Measurement of Consumer Ethnocentrism of Slovak Consumers - Taborecka-Petrovicova, Janka; Gibalova, Maria (International Review of Management and Marketing, 2014)
The conceptualization of consumer ethnocentrism is inferred from the general concept of ethnocentrism which assumes that ethnocentrism starts with the culture into which an individual is born. Over time, the individual will accept the values and behaviour of this particular culture as a norm. However, when the individual becomes aware of other cultures with different values and behaviours, there develops the need of belonging and identification with own culture rather than that of others. When analysing the consumer ethnocentrism, it is also essential to examine whether consumer ethnocentrism operates uniformly across all consumers or there exist some specific factors moderating their ethnocentric tendencies. A lot of studies researching these issues can be found in various cultural contexts, however in Slovakia we found certain gap since there is just a few of them. The aim of the paper is to investigate the level of consumer ethnocentricity of Slovak consumers in general and with the respect to chosen variables – age and gender. The results can serve as an information base for decision-making process of marketing managers focusing especially on local production of domestic products. Keywords: consumer ethnocentrism; CETSCALE; marketing JEL Classifications: M31